Implementation of a big data anonymization system based on Spark - Chaoyi BIAN; Shaomin ZHU; Tao ZHOU (Dianxin kexue)
Group based anonymization is a classical data anonymization framework,which achieves the effect of privacy protection by constructing groups of anonymized data records ensuring that records in the same group cannot be distinguished with each other.The electric power industry big data analysis involves the core data of the power enterprises and the user privacy data,the data sensitivity is stronger,traditional data anonymization systems are unable to meet the needs of big data business applications and safety protection of electric power industry.A new big data anonymization system based on Spark was designed and implemented,which could provide the support for multiple data formats stored on Hadoop and substantially improve the processing efficiency for big data.